The Clinical Spectrum of Rare Inherited Ichthyosis in China: A Review of Thirty-five Cases - Ruiyu Xiang; Xin Huang; Yihe Liu; Shuya Sun; Di Hua; Ran Mo; Yong Yang; Zhiming Chen (Acta Dermato-Venereologica, 2025)
Inherited ichthyosis comprises a spectrum of genetic disorders related to over 50 pathogenic genes. However, there are limited data summarizing the clinical and molecular characteristics of Chinese patients. To broaden the knowledge of clinical and genetic characteristics of inherited ichthyosis and to optimize disease diagnosis and therapies, cases diagnosed with inherited ichthyosis in 1 tertiary centre from 2019 to 2023 were collected, excluding ichthyosis vulgaris and X-linked recessive ichthyosis, genomic sequencing was then performed, and clinical details of the patients were assessed. A total of 35 patients from Jiangsu and Anhui provinces of China were enrolled, 31 of whom were diagnosed with non-syndromic ichthyosis. Within this group, there were cases of autosomal recessive congenital ichthyosis (18/31), epidermolytic ichthyosis (9/31), and superficial epidermolytic ichthyosis (4/31). Additionally, 4 patients were diagnosed with syndromic ichthyosis, comprising 1 case of Chanarin–Dorfman syndrome and 3 cases of Netherton syndrome. The genetic analysis revealed a total of 47 variants across 13 genes, of which 19 were identified as novel variants. This study describes the clinical spectrum of rare inherited ichthyosis in the Jiangsu-Anhui region of China and further expands the genetic characteristics of the disease.